Performance evaluation of charcoal barbeque with air ventilation system - Muhamad Afiqah, Bappu (2019)
The charcoal barbeque system developed in this project is a portable and compact barbecue set equipped with air ventilation system. The objective of this work is to analyses the heat transfer mechanism from barbequing process using this charcoal barbeque system. The main purpose of the air ventilation system is to avoid manual fanning. Besides that, some improvement features are added to reduce combustion time, safety, energy and quality of grilling with ease of use. The methodology involved the design stage of charcoal barbeque with air ventilation system prototype by using NX10 modelling. Subsequently, material selection and cost analysis have been done to identify ideal and cost-effective equipment and material based on price, size/dimension and quality. It followed by the fabrication of major components such as the body casing, charcoal port, hot rack and blower. After that, electrical part was commissioned to control the speed of blower. Three types of performance testing have been conducted to ensure the final product is well function. The blower performance testing proved that the higher the voltage, the higher the velocity. The minimum voltage supply set at 6.9V resulted velocity of blower at 17.7knott (9.1 m/s). Meanwhile maximum voltage 7.3V achieved blower velocity about 21.9knott (11.2m/s). In terms of best quality of charcoal for combustion, coconut shell charcoal is selected as more effective than mangrove wood charcoal as it capable to generate higher hot air temperature, flameless and smokeless. Theoretically, according to the heat transfer analysis, temperature difference throughout the barbecuing determines amount of heat transferred towards the food. This analysis demonstrated that heat is gradually transferred to the chicken meat throughout the barbecuing. The chicken meat received adequate heat at 74.4 °C when it is fully cooked.